Facile synthesis of reduced graphene oxide aerogel in soft drink as supercapacitor electrode - Albarqouni, Yasin M. Y.; Soon, Poh Lee; Ali, Gomaa A. M.; Ethiraj, Anita Sagadevan; Chong, Kwok Feng (Springer Berlin Heidelberg, 2022)
A facile approach is reported to produce reduced graphene oxide (rGO) aerogel. The proposed approach involves the reduction of GO by utilizing the reduction capability of carbonic acid in soft drinks. The presence of carbonic acid reduces the oxygen functionalities in GO to produce rGO and simultaneously provides carboxyl groups for hydrogen bonding in the three-dimensional self-assembly of aerogel. It is also proven that the as-synthesized rGO aerogel possesses a pseudocapacitive effect, owing to the presence of carboxyl groups. This facile reduction approach by an easily available source successfully produces rGO aerogel with 20-fold charge storage capacity enhancement (121 F/g at 0.4 A/g) as compared to the GO. It suggests this facile approach has great potential to construct lightweight graphene aerogel for energy storage applications.